Measured and modelled effect of land‐use change from temperate grassland to Miscanthus on soil carbon stocks after 12 years. Issue 10 (21st May 2019) - Holder, Amanda J.; Clifton‐Brown, John; Rowe, Rebecca; Robson, Paul; Elias, Dafydd; Dondini, Marta; McNamara, Niall P.; Donnison, Iain S.; McCalmont, Jon P.
Abstract: Soil organic carbon (SOC) is an important carbon pool susceptible to land‐use change (LUC). There are concerns that converting grasslands into the C4 bioenergy crop Miscanthus (to meet demands for renewable energy) could negatively impact SOC, resulting in reductions of greenhouse gas mitigation benefits gained from using Miscanthus as a fuel. This work addresses these concerns by sampling soils (0–30 cm) from a site 12 years (T12 ) after conversion from marginal agricultural grassland into Miscanthus x giganteus and four other novel Miscanthus hybrids. Soil samples were analysed for changes in below‐ground biomass, SOC and Miscanthus contribution to SOC (using a 13 C natural abundance approach). Findings are compared to ECOSSE soil carbon model results (run for a LUC from grassland to Miscanthus scenario and continued grassland counterfactual), and wider implications are considered in the context of life cycle assessments based on the heating value of the dry matter (DM) feedstock. The mean T12 SOC stock at the site was 8 (±1 standard error) Mg C/ha lower than baseline time zero stocks (T0 ), with assessment of the five individual hybrids showing that while all had lower SOC stock than at T0 the difference was only significant for a single hybrid. Over the longer term, new Miscanthus C4 carbon replaces pre‐existing C3 carbon, though not at a high enough rate to completely offset losses by the end of year 12. At the end of simulated crop lifetime (15 years), the difference in SOC stocks between the two scenarios was 4 Mg C/ha (5 g CO2 ‐eq/MJ). Including modelled LUC‐induced SOC loss, along with carbon costs relating to soil nitrous oxide emissions, doubled the greenhouse gas intensity of Miscanthus to give a total global warming potential of 10 g CO2 ‐eq/MJ (180 kg CO2 ‐eq/Mg DM). Abstract : Addressing concerns that converting agricultural grassland into the bioenergy crop Miscanthus could negatively impact soil organic carbon (SOC) stocks, we sampled soils (0–30 cm) 12 years after conversion into five Miscanthus hybrids. Year 12 SOC was 8 Mg C/ha lower (significant for a single hybrid) than pre‐planting. A difference of 4 Mg C/ha (15 years after conversion) between modelled land‐use change to Miscanthus and a continued grassland scenario when included in a life cycle assessment (along with carbon costs relating to soil nitrous oxide emissions) resulted in a greenhouse gas intensity of 10 g CO2 ‐eq/MJ.